عقد الوكالة بالاستثمار في المصارف الإسلامية: Wakalah Bi Al-Istithmar in Islamic banks - Alsalman , Jasim Zahir Hamood; bin Hj Abdullah, Luqman; bin Rosele, Muhammad Ikhlas (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2025)
ملخص البحث هدفت الدراسة إلى بيان الوكالة بالاستثمار في المصارف الإسلامية مع بيان مشروعيتها الذي اعتمده الفقهاء المعاصرون، ومتى تكون لازمة وذلك عندما تكون بأجرة؛ مع بيان الفروقات التي اختلفت فيها الوكالة بالاستثمار عن الوكالة التي سطرها الفقهاء في مؤلفاتهم الفقهية وموسوعاتهم العلمية؛ كذلك بيان بعض التطبيقات المصرفية التي اعتمدت في تطبيقها على منتج الوكالة بالاستثمار كأداة استثمارية، ومن خلال الدراسة سنتطرق إلى بعض الإشكالات الفقهية التي قد تشكل على التطبيقات المصرفية كاجتماعها مع بعض العقود المالية كالقرض والهبة والضمان وغيرها من العقود التي قد تكون مطية إلى الربا أو يدخلها الغرر في أحيان كثيرة مما يؤدي إلى المنازعة والتي جاءت الشريعة الغراء من حماية المتعاقدين من الوقوع فيها. ABSTRACT The study aimed to explain the agency for investment in Iran, with an explanation of the legal classification that contemporary jurists have for it, and to classify it from permissibility to obligation in financial transaction contracts, with an explanation of the differences in which the agency for investment differed from the agency that jurists wrote in their jurisprudential books and scientific encyclopedias; It also explains some banking applications that have relied in their application on the investment agency product as an investment tool. Through the study, we will address some of the jurisprudential problems that may arise in banking applications, such as their combination with some financial contracts such as loans, gifts, guarantees, and other contracts that may be a vehicle for usury or are often subject to uncertainty, which leads to disputes, from which the noble Sharia came to protect contracting parties.